Operational Management and Financial Performance of Tourism Industry in Selected Towns of Batangas - Llanes, Lady Grace Violy (Future Science / FSH-PH Publications, 2022)
This study primarily aimed to accomplished four basic objectives, which are: determine the company profiles of tourism businesses at selected towns in Batangas; evaluate the level of effectiveness of the operating management practices of tourism companies in terms of the human resource, marketing and financial management; examine the level of their financial performance in terms of sales growth and profitability; and, find the significant correlation in the respondent’s assessment on the effectiveness of the operational management practices and financial performance of the tourism companies. This study employed the descriptive survey research method that engaged 270 proprietors and managers of different tourism enterprises across the province of Batangas. Convenient sampling technique was used and Statistical Packages for Social Sciences (SPSS) to process the data. The researcher utilized Frequency and Percentage Distribution, Weighted Mean and Pearson Correlation Coefficient. The study revealed that most tourism businesses in selected towns in Batangas belong to Sun and Beach Tourism. Majority are sole proprietorship, with less than three million capitalizations. Years in business operation are mostly 1 to 5 years, with more than 20 employees. Findings illustrate that the majority of tourism businesses of Batangas gave more importance on certain aspects of operational management over the others. For financial management, financial control has been prioritized over financial planning. Marketing management is assessed as one of the most essential aspects of business operation. The study found a very weak to weak correlation in Human Resource, Financial and Marketing Management vs. Sales Revenue Growth and Profitability Growth.